PJMHS 2021
DOI: 10.53350/pjmhs2115113357
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study on Laboratory Profile and Clinical Parameters of Dengue Fever Patients

Abstract: Introduction: Over the past decade, the number of cases of dengue fever has augmented intensely globally. Half the world's population is now under threat. Pakistan has also very high dengue fever per year, with regular reports of dengue outbreaks compared to other countries. Dengue infection should be treated as a solitary ailment with various clinical pictures, vacillating from symptomless situations to severe clinical sequences, which may result in high mortality and morbidity. Aim: To investigate the labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
0
1
Order By: Relevance
“…The number of males and females infected was equal, contrasting the results of earlier reports, where female preponderance was observed (16)(17)(18)(19). This observation also contrasts with other studies that found a higher rate of dengue infection among males (20)(21)(22). Further, we found that most (48.3%) of the infected cases were 20 years of age or less.…”
Section: Discussioncontrasting
confidence: 99%
“…The number of males and females infected was equal, contrasting the results of earlier reports, where female preponderance was observed (16)(17)(18)(19). This observation also contrasts with other studies that found a higher rate of dengue infection among males (20)(21)(22). Further, we found that most (48.3%) of the infected cases were 20 years of age or less.…”
Section: Discussioncontrasting
confidence: 99%